Austria : Publication of Financial Sector Assessment Program Documentation-Technical Note on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Note sets out the findings and recommendations made in the context of the 2019 Financial Sector Assessment Program for Austria in the areas of Anti-Money Laundering/Combating the Financing of Terrorism. It provides a targeted review of Austria's progress in addressing the Money Laundering/Terrorism Financing vulnerabilities. Several initiatives, the amendments introduced to the Financial Markets Anti-Money Laundering Act, the Beneficial Owners Register Act, and other sectoral laws have led to significant enhancements of the legal and regulatory framework which resulted in a number of upgrades on technical compliance ratings by the Financial Action Task Force in the context of the two follow-up reports. The authorities took steps to transpose the Fourth and the Fifth Anti-Money Laundering Directives into national legislation. Steps have been taken to improve the legal and regulatory framework that applies to lawyers, notaries and tax advisors, and other Designated Non-Financial Business and Professions, but there is room for enhancing implementation. The authorities have recently adopted a comprehensive set of reforms to enhance entity transparency, including through the establishment of a Register of Beneficial Ownership.